MEDIA PEMBELAJARAN DIGITAL DALAM MENDORONG KEMANDIRIAN BELAJAR PESERTA DIDIK DI ABAD KE-21 - Keisya Dini Milan Sari; Muchammad Survy Nur Huda; Nadine Qothrunnada Dwihanti; Nezhatian Adi Firmansyah; Surayanah Surayanah (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
The rapid development of digital technology in the 21st century has brought about a significant shift in the educational landscape, particularly in the use of media as a support for the learning process. This article aims to examine the extent to which digital learning media contribute to fostering learner autonomy. This study is built upon a literature review approach by analyzing 15 relevant scholarly sources, including recent journals and academic publications. The analytical technique employed is content analysis, which is used to identify key concepts, recurring patterns, and the interconnections between digital learning media and students’ learning autonomy. The findings reveal that digital learning media hold substantial potential in accelerating learning autonomy through flexible access, interactive learning experiences, and content that aligns with individual needs. The presence of digital media opens opportunities for learners to manage their learning pathways independently, from planning stages to evaluating learning outcomes. However, its effectiveness does not stand alone it is strongly influenced by the precision of the instructional design implemented, the readiness and competence of teachers as facilitators, as well as the availability of technological infrastructure and adequate digital literacy levels. Without well-crafted and measurable pedagogical planning, digital media risk being reduced to merely passive channels of information delivery. Therefore, the use of digital media in learning must be designed strategically and contextually to truly serve as a catalyst for optimal student learning autonomy amid the rapid current of digital transformation. ABSTRAK Pesatnya perkembangan teknologi digital di era abad ke-21 telah menghadirkan pergeseran yang cukup fundamental dalam lanskap pendidikan, terutama dalam hal pemanfaatan media sebagai penunjang proses pembelajaran. Artikel ini hadir dengan tujuan untuk menelaah sejauh mana media pembelajaran digital berperan dalam mendorong tumbuhnya kemandirian belajar pada diri peserta didik. Kajian ini dibangun di atas pendekatan studi literatur dengan menelaah 15 sumber ilmiah yang dipandang relevan, mencakup jurnal-jurnal serta publikasi akademik mutakhir. Adapun teknik analisis yang diterapkan adalah analisis isi, yang difungsikan untuk mengidentifikasi konsep-konsep kunci, pola yang berulang, serta keterkaitan yang terjalin antara media pembelajaran digital dan kemandirian belajar peserta didik. Hasil kajian mengungkapkan bahwa media pembelajaran digital menyimpan potensi yang sangat besar dalam mengakselerasi kemandirian belajar, yakni melalui kemudahan akses yang fleksibel, pengalaman belajar yang interaktif, serta kesesuaian konten dengan kebutuhan masing-masing individu. Kehadiran media digital membuka peluang bagi peserta didik untuk mengelola perjalanan belajar mereka secara otonom, mulai dari tahap perencanaan hingga evaluasi hasil belajar. Meski demikian, efektivitasnya tidak berdiri sendiri ia sangat dipengaruhi oleh kecermatan desain pembelajaran yang diterapkan, kesiapan dan kompetensi guru sebagai fasilitator, serta ketersediaan infrastruktur teknologi dan tingkat literasi digital yang memadai. Tanpa perencanaan pedagogis yang matang dan terukur, media digital berisiko tereduksi menjadi sekadar kanal penyampai informasi yang pasif. Atas dasar itulah, pemanfaatan media digital dalam pembelajaran perlu dirancang secara strategis dan kontekstual agar benar-benar mampu menjadi katalisator kemandirian belajar peserta didik secara optimal di tengah derasnya arus transformasi digital.